DEVELOPING SPEAKING SKILLS THROUGH COMMUNICATIVE ACTIVITIES IN THE ENGLISH CLASSROOM (American Journal of Pedagogical and Educational Research, 2026)
This article examines how communicative activities in English language classes can foster speaking proficiency. It explores the impact of activities such as pair work, group discussions, role-playing, and open speaking exercises on enhancing students' oral abilities. Furthermore, the paper contrasts traditional teaching methods with communicative approaches, explaining the greater effectiveness of communicative techniques in boosting classroom engagement. The research indicates that communicative tasks contribute to learners developing increased self-assurance, participation, and autonomy when speaking English.